2013
DOI: 10.1136/bjsports-2012-091924
|View full text |Cite
|
Sign up to set email alerts
|

Brain activity and perceived exertion during cycling exercise: an fMRI study

Abstract: The present study offers a new approach to assess brain activation during dynamic cycling exercise, and suggests that specific brain areas could be involved in the sensations generating the rating of perceived exertion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
54
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 34 publications
5
54
0
5
Order By: Relevance
“…Based on this, the authors suggested that perception of effort might arise from the primary motor cortex [39]; however, the authors also highlighted the possibility that perceived effort may be associated with activity in neural centres upstream of the primary motor cortex, and possibly even the motor cortex [39,50]. Due to their involvement in homeostatic control, awareness [51], emotion, error detection, motivation and pain [52], higher brain centres such as the insular cortex and cingulate cortex are believed to be extremely important in perceptions that are associated with physical activity [30,53,54]. Supporting this, Fontes et al [30] observed an association between increased neuronal activity in the posterior cingulate gyrus and precuneus and rating of perceived exertion during cycling.…”
Section: Neural Regulation Of Perceptionsmentioning
confidence: 93%
See 3 more Smart Citations
“…Based on this, the authors suggested that perception of effort might arise from the primary motor cortex [39]; however, the authors also highlighted the possibility that perceived effort may be associated with activity in neural centres upstream of the primary motor cortex, and possibly even the motor cortex [39,50]. Due to their involvement in homeostatic control, awareness [51], emotion, error detection, motivation and pain [52], higher brain centres such as the insular cortex and cingulate cortex are believed to be extremely important in perceptions that are associated with physical activity [30,53,54]. Supporting this, Fontes et al [30] observed an association between increased neuronal activity in the posterior cingulate gyrus and precuneus and rating of perceived exertion during cycling.…”
Section: Neural Regulation Of Perceptionsmentioning
confidence: 93%
“…Due to their involvement in homeostatic control, awareness [51], emotion, error detection, motivation and pain [52], higher brain centres such as the insular cortex and cingulate cortex are believed to be extremely important in perceptions that are associated with physical activity [30,53,54]. Supporting this, Fontes et al [30] observed an association between increased neuronal activity in the posterior cingulate gyrus and precuneus and rating of perceived exertion during cycling. Furthermore, an increased activation of the right anterior insular cortex has been documented with increased perceived exertion during dynamic exercise [55,56].…”
Section: Neural Regulation Of Perceptionsmentioning
confidence: 95%
See 2 more Smart Citations
“…While it is appreciably more difficult to perform an exercise-based protocol with PET or fMRI, it is not impossible. A recent exercise study used fMRI to show activations with perceived exertion in healthy individuals [12], and a PET study [13] has shown an insula response during exercise. Although these studies did not measure dyspnoea per se, they've demonstrated proof of concept.…”
mentioning
confidence: 99%